Antimicrobial Resistance and Its Control Policy Implementation in Hospital in Indonesia - Rini Sasanti Handayani; Selma Siahaan; Max Joseph Herman (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan (Journal of Research and Development in Health Services), 2017)
Abstract Antimicrobial Resistance (AMR) is a serious issue because it may reduce treatment effectiveness, increase infection transmission and health care costs. This article aims to identify the problems and the implementation of the AMR control program in hospital. Method :Data were collected by reviewing study results in journals and proceedings, books/literature on AMR at universities and hospitals in Jakarta and Bandung, regulation on the distribution and use of antimicrobials at NADFC, control policy on AMR of MoH RI, as well as data of nosocomial infections from National Survey on Health Facility (Rifaskes 2011). We also conducted consensus decision making which discusses strategic plan and policy for controlling AMR as well as how to optimize or strengthen the strategy with participants involving type A hospital AMR Control Committee as keynote speakers and Directorate of Referral Health Services, Directorate of Health Service Facility, Directorate of Pharmacy Services, Private and Public Hospital Directors in DKI Jakarta, Hospital Accreditation Commission (KARS), others researchers and academicians as stake holders.In Indonesia AMR control program has been started in some hospitals, but there are still many obstacles either from the management, facilities or infrastructures and practitioners. The policies related to AMR control in Indonesia are stated in Law No. 36 of 2009, Law No. 44 of 2009 and the Ministry of Health Decree No. 8 of 2015. There is also a guideline of the Ministry of Health for Infection Control Program in hospital. These policies should be implemented and used as a tool to increase the commitment of the hospital management. Compliance with the guidelines should be strictly implemented, besides the rational prescription of antimicrobials, completing facilities and infrastructures for controlling AMR and the establishment of surveillance of antibiotic use. Keywords: resistance, antimicrobials, hospital Abstrak Resistensi antimikroba (AMR) merupakan masalah serius karena dapat menurunkan efektivitas pengobatan, meningkatkan penularan infeksi dan biaya kesehatan. Tujuan kajian adalah mengidentifikasi masalah dan penerapan program pengendalian AMR di rumah sakit. Hasil dari berbagai penelitian di rumah sakit menunjukkan adanya AMR terhadap beberapa antibiotik. Metode: data berasal dari penelitian dalam jurnal dan prosiding, buku tentang AMR di universitas dan rumah sakit di Jakarta dan Bandung, peraturan tentang AMR di badan POM, kebijakan pengendalian AMR di Kemenkes serta data infeksi nosokomial dari Rifaskes 2011. Kesepakatan keputusan disusun melalui diskusi rencana strategis dan kebijakan pengendalian AMR dan penguatan strategi dengan partisipan ARCP dari rumah sakit tipe A sebagai narasumber dan Direktur Pelayanan Kesehatan Rujukan, Direktur Fasilitas Pelayanan Kesehatan, Direktur Pelayanan Farmasi, direktur rumah sakit pemerintah dan swasta di DKI, Komisi akreditasi rumah sakit, peneliti dan akademisi sebagai pemangku kepentingan. Di Indonesia pengendalian AMR sudah dilakukan di beberapa rumah sakit, tetapi masih banyak kendala baik dari sisi manajemen, sarana, prasarana dan praktisi. Pengendalian resistensi antibiotik di Indonesia diatur berdasarkan peraturan perundang-undangan diantaranya UU No.36 tahun 2009 tentang kesehatan, UU No.44 tahun 2009 tentang rumah sakit, dan Permenkes RI No. 8 tahun 2015. Ada juga pedoman pencegahan dan pengendalian infeksi di rumah sakit yang harus diterapkan guna meningkatkan komitmen pihak manajemen rumah sakit dalam pengendalian AMR. Kepatuhan pada pedoman program pengendalian AMR harus ditekankan, selain peresepan antimikroba yang rasional, pemenuhan sarana dan prasarana untuk pengendalian dan pembentukan surveilans penggunaan antibiotik. Kata kunci: resistensi, antimikroba, rumah sakit